Fabrication and Dosimetric Characterization of Novel Bio-Based Tissue Substitute Phantom Materials - Damilola Oluwafemi Samson, Ahmad Shukri , Mohd Zubir Mat Jafri , Rokiah Hashim , Mohd Zahri Abdul Aziz , Mohd Fahmi Mohd Yusof (International Journal of Advanced Science and Technology, 2020)
construction is the deficiency of standardization background in practice codes for these materials, despite the fact it possess superior properties, such as Ultra-high Performance Fiber Reinforced Concrete (UHPFRC). In this study, Finite Element Analysis (FEA) is utilized to simulate the behavior of UHPFRC and Normal Concrete (NC) simply supported beams under static flexural loading. Abaqus software has been used in which a simplified version of the Concrete Damage Plasticity Model (CDPM) was chosen as a non-linear constitutive model. The model has been validated against conventional CDPM at global (load-deflection) and local (load-stain) levels. Reinforced UHPFRC beam models showed clearly matching response with the validity research paper (reference study) experimental findings. The response of UHPFRC beams has been compared to NC beams. This comparison has been explained in detail and checked with similar material comparisons in the literature. The proposed study has revealed and compared the distribution of cracks in the form of tension and compression damage for both materials. As a conclusion, modelling is an effective way to predict the behavior of concrete beams in which the relative local response was captured in reinforcement bars.